The importance of the TADS course from the perspective of agribusiness and Campo Verde students (Research, Society and Development, 2020)
The main objective of this paper is to investigate the potentialities of the Technologist in Systems Analysis and Development - TADS course at the Federal Institute of Education, Science and Technology of Mato Grosso - IFMT, Campo Verde Reference Center, from the perspective of students of community schools and agribusiness companies located in the municipality. The methodological strategy used to achieve these objectives is qualitative, using and applying questionnaires to students, to collect information to support the view that the school community has regarding this course. In addition, questionnaires were also used in local industries and farms, in order to argue if there is room for Information Technology (IT) professionals and that the knowledge acquired in the course can contribute significantly in the area of agroindustry. At the end of the investigation, a diagnosis is presented to the management of the Campo Verde Reference Center in order to subsidize intervention actions in order to give greater visibility to the TADS course, as well as to promote concrete strategies for the dissemination and presentation of the potentialities The course offers professionals graduating from it, as well as companies in the region that constitute a huge field to be supplied by the skills of these professionals.